Correlation analysis of relations between the interests of senior pupils to teaching subjects and the peculiarities of memory and thinking - Dževečka , A. (Psichologija, 1981)
The relations between senior pupils' interests to teaching subjects and the peculiarities of their memory and thinking were established by the curved line (ŋ) method. The results of the investigation are presented in the form of correlation schemes. Having examined the data of the correlation analysis as well as the analysis of the ways of pupils' memory activities, the author comes to the conclusion that the character of relations between the pupils' interests to teaching subjects and the peculiarities of their memory and thinking depends on the ways of memory activities.
Keywords: interests; memory; thinking